Use of Social Networks in Health Promotion Students in the era of COVID-19 - Espinoza-Portilla, Elizabeth (2021)
Objective. The objective of this article is to describe the use of the social networks (TikTok and Twitter) in medical students at a private Peruvian university, as part of the group activity for the first evaluation of the course: Health Promotion - Determinants. Methods. Descriptive and cross-sectional study, with a quantitative and qualitative focus. All students (60) registered in the course: Health Promotion - Determinants were included. As part of the group activity for the first evaluation, the students were assigned to record a short video which then had to be shared on the TikTok and Twitter platforms. Results. The students made and shared on social networks (TikTok and Twitter) 10 videos on the following topics: promotion of COVID-19 vaccination, promotion of the use of condoms to prevent sexually transmitted infections, prevention of adolescent pregnancy, promotion of use mask and vasectomy promotion. Conclusions. We consider that the promotion of a variety of social networks and digital resources can help the teaching-learning process and the understanding of an increasingly digitized health promotion.